The clinical application of transarterial embolization via radial artery in hemorrhagic diseases in obstetrics and gynecology - Ma, Xueqin; Chen, Hao; Luo, Xiaoping; Wang, Jin; Zhou, Baolin; Liu, Xi (Frontiers in Medicine, 2023)
Purpose The present study aimed to explore the feasibility and safety of Transarterial embolization (TAE) in the treatment of obstetrics and gynecological hemorrhagic diseases transradial approach (TRA) compared to transfemoral approach (TFA). Methods This cohort study was conducted on patients with obstetrics and gynecology bleeding diseases from June 2021 to November 2022. Clinical characteristics of the patients were comparable between the two groups. The success rate of puncture and embolization, radiation dose, operation time, fluoroscopy time (FT), as well as complications of each patient were recorded and then retrospectively analyzed the data. The European Five-dimensional Health Scale (ED-5Q) and visual analog scale (VAS) were used to assess the quality of life (QOL) on the day of discharge and 30 days after surgery between the two groups. Results A total of 71 patients undergoing TAE were allocated to the TRA (n = 31) or TFA (n = 40) group in this study. Puncture and embolization were completed in all patients. Compared to the TFA group, the radiation dose of the TRA group (343.89 ± 108.81 mGy vs. 469.29 ± 198.66 mGy; p = 0.029) is significantly reduced. Minor complications occurred in only one patient (3.2%) in the TRA group. The surgery-related quality of life EQ-5D index score on the day of discharge in the TRA group (0.72 ± 0.12 vs. 0.65 ± 0.11; p = 0.017) was significantly higher than that in the TFA group, and the VAS score (2.55 ± 0.62 vs. 2.95 ± 0.85; p = 0.025) of catheter site discomfort was significantly lower in the TRA group were than in the TFA group, but no significant difference was observed in the QOL assessment at 30 days post-surgery. Conclusion Transradial approach TAE has comparable efficacy and safety to TFA TAE in treating obstetrics and gynecological bleeding diseases. This access can improve patient QOL without affecting surgical safety.